PENINGKATAN PRODUKSI DAN PENJUALAN PADA USAHA BOLEN PISANG “QIFA BAKERI” DI SEMEMI KIDUL-BENOWO-SURABAYA - Maulana, Alfin; Fitryani, Fitryani; Novantori, Hafizh; Herdiansyah, Nova (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
The business of making bread and moist cakes is a home-based endeavor that many people engage in within the Sememi Kidul-Benowo-Surabaya area. The high demand for bread and moist cakes presents a promising business opportunity. The tight competition requires the production of bread and moist cakes to actively engage in breakthroughs and innovations, so that their products remain appealing to consumers. The effort of producing bread and wet cakes as a small business also faces various challenges, including low turnover and production capacity, as well as weaknesses in marketing, particularly in the distribution channels for its products. This community service activity is carried out at a bakery and wet cake business called